Comunidades virtuais e as organizações: um estudo sobre a utilização deste novo ambiente - Ferreira, Carlos Eduardo Coelho (2008)
Since the end of the 20th century, the virtual and the real worlds coexist. One should not understand the virtual as the opposite for real, something that does not exist, but as something that is equivalent. The virtual is a simulation of the reality, not its negation. Organizations look for to adapt themselves to this new reality of the coexistence of two worlds and adopt new technologies that will allow them to develop in the virtual world the activities that they handle in the real world. This dissertation makes a revision of some aspects that collaborate for the construction of the concept of virtual community, among others presenting the community of practice, the virtual environment, the metaverse, the virtual organization, the real and the virtual. It does not intend to deplete the subject, what would be impossible, but to present it under an academicscientific approach. The general objective of this research was to identify the factors of attraction of the organizations to the virtual communities and to identify the main strategies used by the organizations in their interaction in the virtual environment. The research identified the main characteristics and functionalities that attract the organizations for the virtual world. To assure rigor, this study was written under the qualitative research, descriptive case study methodology. Many corporations of the real world were identified with initiatives in the metaverse, but it was not possible to identify if part of these organizations had made it only for mimetic, to follow a movement commanded by advertisement agencies. As an objective result of this research, it is possible to affirm that organizations had detected the changes of the development of the virtual environment, and for consequence of the virtual communities, and already are promoting experiments in the metaverses with the clear intention to learn as these virtual worlds mature.